1997
DOI: 10.1021/bi970006+
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Actinorhodin Polyketide Synthase Acyl Carrier Protein from Streptomyces coelicolor A3(2),

Abstract: The solution structure of the actinorhodin acyl carrier protein (act apo-ACP) from the polyketide synthase (PKS) of Streptomyces coelicolor A3(2) has been determined using 1H NMR spectroscopy, representing the first polyketide synthase component for which detailed structural information has been obtained. Twenty-four structures were generated by simulated annealing, employing 699 distance restraints and 94 dihedral angle restraints. The structure is composed, principally, of three major helices (1, 2, and 4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 47 publications
6
135
0
1
Order By: Relevance
“…5, B-E. Although the rat FAS ACP forms the conserved ␣-helical bundle structure common to all ACPs, there is a slightly lower degree of ␣-helical content (46% over residues 2114 -2192) than other ACPs (E. coli FAS ACP 50% (39,40), S. cerevisiae ACP (50%) (41), B. subtilis FAS ACP 60% (42), and the actinorhodin PKS ACP 50% (12)). The shorter helices are replaced instead by the longer loop regions in the rat FAS ACP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, B-E. Although the rat FAS ACP forms the conserved ␣-helical bundle structure common to all ACPs, there is a slightly lower degree of ␣-helical content (46% over residues 2114 -2192) than other ACPs (E. coli FAS ACP 50% (39,40), S. cerevisiae ACP (50%) (41), B. subtilis FAS ACP 60% (42), and the actinorhodin PKS ACP 50% (12)). The shorter helices are replaced instead by the longer loop regions in the rat FAS ACP.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the low resolution solution phase structure of the isolated rat FAS apoACP domain (10) and found it to adopt an ␣ helical bundle structure consistent with the Type II ACPs from fatty acid (11) and polyketide synthases (PKSs) (12). Furthermore, it has been shown that the rat FAS ACP can sub-stitute for the E. coli FAS ACP (13) in vivo and that it is recognized as a substrate by enzymes known to modify Type II ACPs including Streptomyces coelicolor holo-ACP synthase (ACPS) and malonyl-CoA:ACP transacylase in vitro (10).…”
mentioning
confidence: 95%
“…It is unclear whether this inhibition reflects interactions between the apoACP protein and MAT or KS/CLF or both. Since the solution structures of several Type II ACPs have been solved (31)(32)(33)(34)(35)(36)(37)(38), further studies into the structural basis for these molecular recognition properties could provide fundamentally new insights into the importance of protein-protein interactions in regulating Type II PKS function and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…To study the ACP binding ability of FabG and FabG mutants, 1 M biotinylated ACP was incubated with different concentrations (30 nM to 2 M) of Histagged FabG at room temperature in a 384-well ProxiPlate (Packard Instrument Co.). After a 30-min incubation, streptavidin donor beads and nickel chelate acceptor beads (50 g/ml final concentration for each bead, (His) 6 Tag detection system, Packard Instrument Co.) were added to the above solutions. The reaction mixtures were then incubated for 1 h before being read by Fusion TM Universal Microplate Analyzer (Packard Instrument Co.), with excitation at 680 nm and emission at 600 nm.…”
Section: Materials-amershammentioning
confidence: 99%